LIFETIME ANALYSIS OF SPHERICAL ROLLER BEARINGS ON ROLL MILL MACHINES AT PT. ABC - Jannah, Miftahul; Wahyudi, Hadi; Aswata, Aswata; Susilo, Sidik; Alhamidi, A. Ali; Ardiansyah, Fakhri (Trends in Mechanical Engineering Research, 2024)
PT ABC is a wheat flour production company in Indonesia. Many sophisticated machines are used in the wheat flour production process, one of which is the roll mill machine. In its operation, the roll mill machine uses bearings to support the roll when it rotates and reduce friction that occurs so that the roll can rotate smoothly and avoid wear. If the bearing does not function properly, it can damage the machine and other components. Therefore, to predict damage to the bearing, it is necessary to analyze how long the bearing lifetime is. In the implementation of this Practical Work, research will be conducted to determine the lifetime and types of damage that occur to the bearings used so that solutions can be found to prevent damage to the machine and other components. Based on the results of calculations in this study, the life of the spherical roller bearing in the roll mill machine using the basic rating life method shows that the bearing life obtained is 36,696,343 operational hours, while the time required to re-lubricate the spherical roller bearing is every 9800 hours with the amount of lubricant given is 17.6 grams.